KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS ANEKDOT DENGAN KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS X SMK NEGERI 1 LUBUK BASUNG - Izmi, Nur; Basri, Irfani; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThe article was written to illustratethe correlation between students ability inreading comprehension of anecdotetext with the skill of writing anecdote texts of tenth grade students in SMK N 1 Lubuk Basung. This research is a quantitative research using descriptive methods. The researchdesign used correlational. The population in this study were tent